Gibi construction as a facilitator of the geography teaching learning process - Diniz, Ana Cláudia Araújo; Ribeiro Fortes, Mircia (Revista Ensino de Geografia (Recife), 2019)
This paper aims to present the report of a proposal for the constructionof comic books in geography teaching, as a facilitator of the teaching-learning process to approach the city-country theme. There is a certain perspective in the teaching of geography basedsimply on a constant mnemonic, a fact that does not collaborate with meaningful learning for life in society and also does not arouse the student's interest in geography as a school subject, as the way It is worked on in the routine of systematized Therefore, we intend to present the importance of the use of didactic-pedagogical tools in the teaching and learning process of geography in higher education, considering the need to redefine the temporal-spatial relationship, in favor of education and geographical reasoning that provide individuals a new positioning to criticality and reflection. However, such tools cannot be used as hangers, but rather as a means for the geography teaching process. From the construction of comics we find that the methodology isa stimulus in the teaching-learning process of geography, becausethe text and drawing express the creativity, reflection and perception of students